FORMATION STRATEGY COGNITIVE MEANINGS AS A FACTOR PROFESSIONAL TRAINING TEACHERS OF ART DISCIPLINES (Pedagogy of Higher and Secondary Education, 2022)
In article processes of an intensification of vocational training of the teacher of art in a context of modem strategy of training are considered It is accented oft expediency of comprehension of value of strategy of fomiation cognitive senses a universal principle of cognitive activity; the principles classified to an operational attribute are allocated; groups of these principles are considered in quality constrm strategy cognitive development of the person.
Keywords: teacher of art; cognitive senses; strategic principles of training; cognitive circuits; resinification.